Does Kangaroo care affect the weight of preterm/low birth-weight infants in the neonatal setting of a hospital environment?. Issue 4 (August 2018) - Cunningham, Colette; Moore, Zena; Patton, D.; O'Connor, T.; Nugent, Linda E.
Abstract: The aim of this systematic review is to ascertain if kangaroo care (KC) affects the weight of preterm/LBW infants in the neonatal setting of hospital environments. The following databases were searched: PubMed, The Cochrane Library, The Cumulative Index to Nursing and Allied Health Literature, Web of Science, Embase and SCOPUS. Search terms include: kangaroo care, kangaroo mother care, kangaroo ward care, skin to skin care, skin to skin contact, skin to skin mother care, weight, neonatal infant, neonatal care and neonatal unit. 10 RCT's demonstrated that KC increases weight of preterm/LBW infants in the neonatal setting of a hospital environment. 7 quantitative studies also reported an increase in weight. Increased rates of breastfeeding were also consistently associated with regard to KC across the 17 studies. KC effects weight gain of preterm/LBW infants in the neonatal setting of a hospital environment. Exclusive breastfeeding rates were positively influenced through KC.